LAYANAN BIMBINGAN KELOMPOK DALAM MENCEGAH CYBERBULLYING GENERASI ALPHA - Finayanti, Juwita; Christiana, Ratih; Suharni, Suharni (Jurnal Muria Research Guidance and Counseling (MRGC), 2024)
Group guidance services are one of the efforts of the guidance and counseling service program, which in the process utilizes group dynamics as a form of guidance effort by providing information about cyberbullying so that students, especially the alpha generation, receive preventive measures and an understanding of what cyberbullying is. The alpha generation is a generation that was born and grew up with advances in digital technology. The development of digital technology is a phenomenon that is inseparable from the development of the lives of the alpha generation. For this reason, it is important that the alpha generation is equipped with insight and knowledge about what cyberbullying is so that they can anticipate the impact of cyberbullying